The Effect of Health Education with Pictorial Quizmedia on Knowledge of First Aid for Burns - Rahmawati, Lilis; Al Hasbi , Habid; Rosiana Ulfah, Hana; Sarwoko, Sarwoko; Suyatna, Suyatna (Asy-Syifa : Journal of Science and Technology Nursing, 2024)
Purpose: This study aims to determine the effect of health education with illustrated quiz media on first aid knowledge in vocational high school students. Methods: This study uses a type of quantitative research using a Pre-experimental design with a One-Group Pretest-Posttest design approach. Pre-experimental design with One-Group Pretest-Posttest design approach.  Results: This study used a sample of 75 respondents in grade 11. Method of collecting burn first aid knowledge data was collected by picture quiz. Based on wilcoxon test, statistically significant increase in knowledge of P-value = 0.00 <0,05. The mean pre-test was 6.29 and post-test was 9.00. Conclusion: There is an effect of health education with illustrated quiz media on the knowledge of first aid for burns in vocational high school students.